2018
DOI: 10.24926/iip.v9i2.985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist-Led Diabetes Management in Primary Care Clinics

Abstract: Purpose: Current literature supports that pharmacists effectively lower hemoglobin A1c (HbA1c) in diabetic patients. Little data exists on pharmacists’ effects on comorbidity management, patient satisfaction, or financial viability of these positions. This study looked to assess the impact of pharmacists on diabetes management compared to usual care. Methods: This multi-site, two-part study includes a retrospective chart review of patients referred to the pharmacist versus usual care within a large acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…14 Collaborative practice agreements provide pharmacists the ability to manage chronic disease states in collaboration with physicians to improve patient outcomes and patient satisfaction. 5,[14][15][16] The involvement of clinical pharmacists in direct patient care has been shown to improve clinical outcomes in many chronic disease states, including but not limited to diabetes, hypertension, and dyslipidemia. 2,[6][7][8][9]12,13,[16][17][18][19][20] Data also supports that clinical pharmacy services improve provider work-life 21 and reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Collaborative practice agreements provide pharmacists the ability to manage chronic disease states in collaboration with physicians to improve patient outcomes and patient satisfaction. 5,[14][15][16] The involvement of clinical pharmacists in direct patient care has been shown to improve clinical outcomes in many chronic disease states, including but not limited to diabetes, hypertension, and dyslipidemia. 2,[6][7][8][9]12,13,[16][17][18][19][20] Data also supports that clinical pharmacy services improve provider work-life 21 and reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…5,[14][15][16] The involvement of clinical pharmacists in direct patient care has been shown to improve clinical outcomes in many chronic disease states, including but not limited to diabetes, hypertension, and dyslipidemia. 2,[6][7][8][9]12,13,[16][17][18][19][20] Data also supports that clinical pharmacy services improve provider work-life 21 and reduce health care costs. 12,13,16,17,22,23 Matzke et al 17 found that the inclusion of clinical pharmacists in a collaborative care model demonstrated significant improvements in glycosylated hemoglobin, blood pressure, low-density lipoprotein (LDL) cholesterol, and total cholesterol in the collaborative care group compared with the usual care group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Furthermore, another study found a large HbA1c reduction in patients who enrolled in the pharmacist-management group compared to usual care. 27 In our study, the APh made independent therapeutic decisions during patient visits. The primary care physicians at the clinic did not change any of the therapeutic decisions made by the APh.…”
Section: Discussionmentioning
confidence: 92%
“… 26 Furthermore, another study found a large HbA1c reduction in patients who enrolled in the pharmacist-management group compared to usual care. 27 …”
Section: Discussionmentioning
confidence: 99%